ナンキョク ショウワ キチノ イチ ト ヒョウコウ - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1993)
P(論文) 南極・昭和基地のいろいろな観測点の位置や標高は, それぞれ異なる値が使われている。近年, 測地衛星を用いた測位システムが発達し, 南極でも用いられている。将来の混乱を防ぐため, 昭和基地のいろいろな点での位置や標高がどのように求められたかを明らかにする。その主なものは以下のとおりである。1) 気象観測点, 地磁気観測点の位置としては天測点の値が使われている。2) 振子測定による重力基準点, 地震計室の位置と標高は基準点測量と水準測量で決められている。3) 地学棟内重力点, 国際絶対重力基準点, 験潮場の位置と標高は地形図(東オングル島1 : 5000)で刺針し, 水準測量で決められている。 Many reports concerning the locations and elevations of Syowa Station, Antarctica, have been published. Here previous data are noted for future reference. All data presented in this report were surveyed from the astronomical geodetic point which was established in 1957. The details are as follows : 1) The locations of meteorological and geomagnetic observations are used the location of the astrnomical geodetic point. 2) The locations of the pendulum gravity station and seismic vault were determined by surveying and leveling from the astronomical geodetic point. 3) The locations of the gravity point in the Earth Science Laboratory, the absolute gravity point and the tide gauge were determined from the geographical map of East Ongul Island (1 : 5000), Antarctica. Elevations of those points were determined by leveling from the tide gauge reference point. departmental bulletin paper